Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Cardiac Physiology and Pathology" - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Cardiac Physiology and Pathology" ABS 1. EVALUATION OF THE RELATIONSHIP BETWEEN PATENT DUCTUS ARTERIOSUS AND THE PLATELET MASS INDEX IN PRETERM INFANTS • M. Kara, İ. Caner, K.Ş. Tekgündüz, İ. Polat, H. Keskin ABS 2. DIAGNOSIS OF DIGEORGE SYNDROME: THE CONTRIBUTION OF MOLECULAR GENETICS • Y. Halleb, H. Hadj-Abdallah, S. Nouri, A. Touati, M. Bellallah, J. Mathlouthi, N. Mahdhaoui, H. Sboui, A. Saad, D. H'mida ABS 3. ASSOCIATION BETWEEN SIZE OF PATENT DUCTUS ARTERIOSUS AND CO-MORBIDITIES • S. Bellis, Y. Singh ABS 4. EFFICACY OF MEDICAL TREATMENT IN CLOSING PATENT DUCTUS ARTERIOSUS IN ELBW INFANTS • S. Bellis, Y. Singh ABS 5. ACETAMINOPHEN FOR CLOSING PDA. SHOULD IT BE A FIRST LINE THERAPEUTIC OPTION? • I. Tofé, M.D. Ruiz, M.P. Jaraba, M.V. Rodriguez, R.L. Rueda, M.D. Ordoñez, M.J. Parraga ABS 6. PATENT DUCTUS ARTERIOSUS WITH HEMODYNAMIC REPERCUSSION IN VERY LOW WEIGHT PRETERM INFANTS TREATED WITH ORAL IBUPROFEN PRESENTS A HIGH RATE OF BRONCHOPULMONARY DYSPLASIA • M.M. Lourenço, E. Sacramento, F. Carmona, C. Calixto, F. Martin-Celini, G.H. Seribelli, W.A. Gonçalves-Ferri ABS 7. EFFECTIVENESS OF INDOMETHACIN, IBUPROFEN AND PARACETAMOL FOR PATENT DUCTUS ARTERIOSUS (PDA) IN PRETERM INFANTS: A NETWORK META-ANALYSIS • S. Mitra, I.D. Florez, M.E. Tamayo, Y. Zhang, B. Sadeghirad, A.M. Zea, L. Mbuagbaw, T. Vanniyasingam, L. Thabane ABS 8. PRENATAL DIAGNOSIS OF THE SYSTEMIC BLOOD FLOW RESTRICTION DEFECTS IMPROVES HEMODYNAMIC STABILITY OF THE NEONATES WITH CONGENITAL CARDIAC DEFECT AT THE ADMITTANCE IN NEONATAL INTENSIVE CARE UNIT •  M. Cucerea, M. Simon, M. Ungureanu, R. Marian, E. Moldovan, M. Rusneac, C. Gliga, L. Suciu ABS 9. ASSOCIATION BETWEEN ASYMPTOMATIC PATENT DUCTUS ARTERIOSUS BEYOND THE EARLY POSTNATAL PERIOD AND 3-YEAR NEUROLOGICAL OUTCOME • K. Inomata, S. Taniguchi, T. Inoue, A. Kawase, Y. Kondo ABS 10. THE USE OF SPECKLE TRACKING ECHOCARDIOGRAPHY TO ASSESS MYOCARDIAL PERFORMANCE IN MONOCHORIONIC DIAMNIOTIC TWINS WITH AND WITHOUT TWIN TO TWIN TRANSFUSION SYNDROME • C.R. Breatnach, A.T. James, F. Malone, N. McCallion, O. Franklin, A. EL-Khuffash ABS 11. INCIDENTAL FINDINGS ON ROUTINE TARGETED NEONATAL ECHOCARDIOGRAPHY PERFORMED IN PRETERM INFANTS LESS THAN 29 WEEKS GESTATION • A. Smith, C.R. Breatnach, A.T. James, O. Franklin, A. El-Khuffash ABS 12. A CLINICAL SCORING SYSTEM AS A DIAGNOSTIC TOOL FOR HEMODYNAMICALLY SIGNIFICANT PATENT DUCTUS ARTERIOSUS IN PRETERM INFANTS • N. Okur, H.G. Kanmaz, M. Buyuktiryaki, G.K. Simsek, F.E. Canpolat, N. Uras, S.S. Oğuz ABS 13. THE SUDDEN CHANGE IN CARDIAC FUNCTION AFTER PATENT DUCTUS ARTERIOSUS LIGATION MEASURED BY ELECTRICAL CARDIOMETRY IN AN EXTREME LOW BIRTH WEIGHT INFANT • Y.H. Chien, K.Y. Chao, Y.L. Chen, L.Y. Tsai, C.E. Chiang, S.C. Mu ABS 14. HEMODYNAMIC CHANGES RELATED TO DUCTUS CLOSURE IN PRETERMS • A. Rodríguez Sánchez de la Blanca, N. González Pacheco, C. Ramos Navarro, M. Arriada Redondo, N. Navarro Patiño, E. Sanz López, M. Sánchez Luna ABS 15. NOVEL METHODS TO CHARACTERIZE RIGHT VENTRICULAR - PULMONARY ARTERIAL COUPLING IN EXTREME PRETERM INFANTS WITH LATE ONSET PULMONARY HYPERTENSION • P. Levy, M. Patel, S. Choudhry, M. Holland, T. Sekarski, A. Hamvas, G. Singh ABS 16. EMERGING QUANTITATIVE ECHOCARDIOGRAPHIC MARKERS OF PULMONARY VASCULAR DISEASE AND RIGHT VENTRICULAR DYSFUNCTION IN EXTREME PRETERM INFANTS WITH LATE PULMONARY HYPERTENSION • P. Levy, C. Brennan, M. Patel, S. Choudhry, A.A. Sanchez, A. EL-Khuffash, C. Breatnach, O. Franklin, A. Hamvas, G. Singh ABS 17. TREATMENT FOR PATENT DUCTUS ARTERIOSUS IN PRETERM INFANTS - LESS IS MORE? • T. Hundscheid, W. de Boode ABS 18. PULSE OXIMETRY SCREENING IN THE ASYMPTOMATIC NEWBORNS • S. Chaudhry, Y. Singh ABS 19. CHANGES IN THE MANAGEMENT OF PATENT DUCTUS ARTERIOSUS OVER 10 YEARS IN A TERTIARY NEONATAL CENTRE • D. Panjwani, S. Mittal ABS 20. COARCTATION OF THE AORTA - THE CONGENITAL HEART DEFECT WITH A MILLION FACES • M. Simon, R. Sánta, L.M. Suciu, Z.S. Gáll, R. Marian, M. Rusneac, C. Gliga, M.C. Cucerea ABS 21. RARE CONGENITAL MITRAL VALVE MALFORMATION • R. Stroescu, A. Popoiu, M. Gafencu, O. Marginean, G. Doros ABS 22. COINCIDENTAL LEFT ATRIAL THROMBUS • I. Mungan Akin, P. Canizci, S. Sevuk Ozumut, S. Arslanoglu ABS 23. IBUPROFEN AND INDOMETHACIN DIFFERENTIALLY REGULATE VEGF AND ITS RECEPTORS IN DUCTUS ARTERIOSUS ENDOTHELIAL CELLS • H. Sallmon, S. Akanbi, S.C. Weber, A. Gratopp, C. Rheinländer, P. Koehne ABS 24. PERICARDIAL EFFUSION: SEVERE COMPLICATION OF CENTRAL VENOUS CATHETERIZATION IN THE NEWBORN (REPORT OF 12 SURVIVORS) • S. Nouri Merchaoui, J. Methlouthi, H. Ayache, M. Bellalah, I. Kacem, H. Barbouche, A. Ghith, N. Mahdhaoui, H. Seboui ABS 25. GENETIC ABNORMALITIES AND CONGENITAL HEART DISEASE • S. Nouri Merchaoui, J. Methlouthi, H. Ayech, M. Bellaleh, I. Kacem, H. Barbouche, A. Ghith, S. Mougou, D. Hmida, N. Mahdhaoui, H. Seboui ABS 26. USE OF PROSTIN IN A TERTIARY NEONATAL UNIT • R. Prasad, H. Wood, O. Nolan, S. V. Rasiah ABS 27. THE USABILITY OF ICON FOR NEONATOLOGY • W.P. de Boode, B.M. Wulterkens, B.A.M. Nieuweweme ABS 28. ASSESSMENT OF NEONATAL HEART RATE IMMEDIATELY AFTER BIRTH USING DIGITAL STETHOSCOPE, HAND HELD ULTRASOUND AND ELECTROCARDIOGRAPHY • B. Treston, J. Semberova, R. Kernan, E. Crothers, A. Branagan, N. O'Cathain, J. Miletin ABS 29. NEW IBUPROFEN DOSAGE REGIMEN FOR PATENT DUCTUS ARTERIOSUS FOLLOWING SIMULATIONS BASED ON PHARMACOKINETIC-PHARMACODYNAMIC EVIDENCE •  R. Flint, R. ter Heine, E. Spaans, D. Burger, J. de Klerk, K. Allegaert, C. Knibbe, S. Simons ABS 30. WHAT IS THAT PULSATING ON THE ANTERIOR ABDOMINAL WALL? •  O. Nolan, R. Prasad, P. Miller, M. Singh, S.V. Rasiah